2010
DOI: 10.1074/jbc.m110.116285
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Elements of a Maize γ-Zein Domain Involved in Protein Body Biogenesis

Abstract: The N-terminal proline-rich domain of ␥-zein (Zera) plays an important role in protein body (PB) formation not only in the original host (maize seeds) but in a broad spectrum of eukaryotic cells. However, the elements within the Zera sequence that are involved in the biogenesis of PBs have not been clearly identified. Here, we focused on amino acid sequence motifs that could be involved in Zera oligomerization, leading to PB-like structures in Nicotiana benthamiana leaves. By using fusions of Zera with fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 66 publications
2
79
0
1
Order By: Relevance
“…However, the high importance of the first two N-terminal Cys in Zera-ECFP was not confirmed in full-length γ-zein: mutagenesis of these residues in Zera-ECFP resulted in full secretion (Llop-Tous et al, 2010), whereas 5C γ-zein is largely insoluble and ER-located, and it is almost unavailable for secretion. This indicates that the contribution of individual Cys residues of the N-terminal region to PB formation are less strict in full length γ-zein, as also suggested by domain deletion experiments (Geli et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high importance of the first two N-terminal Cys in Zera-ECFP was not confirmed in full-length γ-zein: mutagenesis of these residues in Zera-ECFP resulted in full secretion (Llop-Tous et al, 2010), whereas 5C γ-zein is largely insoluble and ER-located, and it is almost unavailable for secretion. This indicates that the contribution of individual Cys residues of the N-terminal region to PB formation are less strict in full length γ-zein, as also suggested by domain deletion experiments (Geli et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In maize, γ-zein contains six cystein residues, and N-terminal Cys 7 and Cys 9 are critical for oligomerization and PB formation. 10) Kawagoe reported that the formation of intermolecular disulfide bonds between the CCxQL motif and the PxxC motif of prolamin play an important role in polymerization in rice PB-Is. 18) On the other hand, 13b prolamin has no cystein residue, and 13b prolamin-GFP fusion proteins formed PB-Ilike structures in rice calli in our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Once PBs arise, they grow in size over time (Figure 1B), reaching their maximum size at 5 days post infiltration (dpi) for GFP‐ELP and GFP‐HFBI (Saberianfar et al ., 2015), and at 10 dpi for Zera®‐ECFP (Llop‐Tous et al ., 2010). In all cases, PB growth is accompanied by an increase in accumulation levels of the respective recombinant protein.…”
Section: Pb Formation Initiates Upon Reaching a Threshold Levelmentioning
confidence: 99%
“…This strategy, however, does not work as well with Zera®, because the strong affinity of Zera® molecules to one another results in a condensed and sticklike alignment of Zera® molecules which excludes other molecules from the core of PBs (Llop‐Tous et al ., 2010). This was confirmed with co‐expression of secretory GFP or ER‐targeted GFP with Zera®‐DsRed in which the GFP signal localized to the periphery of Zera® PBs and not in their core, and explains why Zera®‐DsRed has no significant effect on EPO accumulation (Saberianfar et al ., 2016).…”
Section: Proteins Are Sequestered Passively Into Some But Not All Pbsmentioning
confidence: 99%
See 1 more Smart Citation